Measuring the impact of crises in the horticultural sector: the case of Spain. Issue 5 (3rd June 2019) - Pérez-Mesa, Juan Carlos; Serrano-Arcos, María del Mar; Sánchez-Fernández, Raquel
Abstract : Purpose: The purpose of this paper is to review the literature on image crises in the food industry as well as provide a diachronic analysis to distinguish between the varying types of crises that played a critical role in the horticultural sector in recent decades, focussing on the particular case of Spain as the largest horticultural exporter in Europe. This research also analyses the economic impact of these crises upon demand. Design/methodology/approach: An empirical analysis has been conducted using inverse demand models to determine the prospective impact on demand of the image crises in the main European destination markets. Findings: The empirical analysis reveals an immediate impact upon demand (imports) in the short term. Sector crises invariably have one or many "explosion" points when they reach the public sphere. These events reduce demand among European consumers, ultimately leading to a decrease in imported goods. The tested models revealed considerably significant losses that subsequently reduce annual exports by more than 3 per cent. The analysis also reveals strong effects of complementarity and substitution among the various products that comprise the horticultural supply. Research limitations/implications: This study has not taken into account several movements that have also affected the horticultural sector, such as "anti-consumption" and boycotts. Empirical results reveal a strong impact of image crises on demand (imports) in the short term. Consequently, there is an evident need to undertake actions, managed from the supply origin, that reach the consumer and effectively re-establish the prestige of the Spanish production system. Practical implications: This paper highlights the importance of the mass media in consumer attitudes and perceptions, and the need to create channels of direct communication to break the information asymmetry between production and consumption areas. Originality/value: This paper sheds new light on the literature of image crises. The findings of this research have contributed to greater knowledge of how image crises influence demand. From the point of view of management, these results can have practical implications for the highly competitive sector of horticultural production.